The causal relationship between gut microbiota and lymphoma: a two-sample Mendelian randomization study - Li, Biyun; Han, Yahui; Fu, Zhiyu; Chai, Yujie; Guo, Xifeng; Du, Shurui; Li, Chi; Wang, Dao (Frontiers in Immunology, 2024)
Background: The association between gut microbiota and lymphoma has been established, but the causal relationship between them remains unclear.Methods: A two-sample Mendelian randomization (MR) was used to analyze the causal relationship between gut microbiota and lymphoma. Microbiome data (n = 14,306) and lymphoma (n = 324,650) data were both sourced from European populations. Single nucleotide polymorphisms (SNPs) were selected as instrumental variables based on several criteria. We employed various MR methods, such as the inverse variance weighted (IVW) method, to evaluate the causal effect between exposure and outcomes and conducted sensitivity analyses to validate the heterogeneity and pleiotropy of the instrumental variables.Results: In the MR analyses using the IVW method, we identified 38 causal relationships between genetic liability in the gut microbiome and 5 types of lymphoma, including those involving the family Bifidobacterium and genus Lactobacillus. A few of the more significant results are as follows. Genus.Coprobacter (OR = 0.619, 95%CI 0.438-0.873, P = 0.006) exhibited suggestive protective effects against Hodgkin's lymphoma. Genus.Alistipes (OR = 0.473, 95%CI 0.278-0.807, P = 0.006) showed a negative association with the risk of diffuse large B-cell lymphoma. Genus.Ruminococcaceae (OR = 0.541, 95%CI 0.341-0.857, P = 0.009) exhibited suggestive protective effects against follicular lymphoma. Genus.LachnospiraceaeUCG001 (OR = 0.354, 95%CI 0.198-0.631, P = 0.0004) exhibited suggestive protective effects against T/NK cell lymphoma. The Q test did not reveal heterogeneity, the MR-Egger test showed no significant intercepts, and the leave-one-out (LOO) analysis did not discover any SNP that affect the results.Conclusion: This study reveals a causal relationship between the gut microbiota and lymphoma and identifies potential causative and probiotic taxa that influence lymphoma pathogenesis, which provide new ideas for possible therapeutic approaches to lymphoma and clues to the pathogenesis of lymphoma.